A method for assessing the life cycle costs of modifications to ballasted track systems. (10th December 2020) - Rempelos, Georgios; Ortega, Alejandro; Blainey, Simon; Preston, John; Le Pen, Louis; Armstrong, John
Highlights: LCC model for assessing the impact of modifications to ballasted track systems. LCC model integrated with the results of element tests and applied to RFRs and USPs. The LCC implications of installing RFRs and USPs at renewal were investigated. Modifications of ballasted track delivers significant long-term track quality improvements. Improvements of inherent track quality lead to considerably reduced LCC. Abstract: Tests can be carried out on elements of railway track in a laboratory to assess the potential for particular ballast and sleeper combinations to alter stiffness, reduce settlement, and improve the transfer of stresses between sleeper and ballast. For example, under sleeper pads (USPs) and random fibre reinforcements (RFRs) have been shown to reduce settlement in such tests. However, it is more problematic to apply test results to predict real world field rates of deterioration along the track geometry which is largely a function of differential settlement. This is important, because an understanding of reductions in real world rates of deterioration is necessary to predict life cycle costs (LCC) of such interventions and assess the economic case for altering current practice. This research examines the impact of installing USPs and RFRs on two different routes in the UK: the London-Portsmouth line and a section of the East Coast Main Line (ECML). A simple methodology, based on relative settlement is proposed to adapt the results of laboratory element tests into a suitable parameter for input into the track geometry degradation model, allowing estimation of LCC. The financial savings from installation were found to be slightly higher for the ECML than the Portsmouth line, and higher for USPs than for RFRs. Although these conclusions are based on a UK case study, they could be applicable to any ballasted railway track operation in a developed region facing high maintenance costs and growing demand.